Risk factors of intracranial stenosis among older adults with acute ischemic stroke - Pinzon, Rizaldy; Asanti, Laksmi; Sugianto, Sugianto; Widyo, Kriswanto (Universa Medicina, 2009)
Intracranial large artery atherosclerosis is an important cause of stroke worldwide. Previous studies have shown that it is found more commonly in Asians. However, studies of intracranial stenosis in Indonesian stroke patients have been very few in number. The aim of this cross-sectional study was to determine the frequency and risk factors of intracranial stenosis in acute ischemic stroke. The data were obtained from 234 consecutive patients in the transcranial doppler (TCD) registry. Documentation of risk factors was performed systematically and for TCD sonography TD-DOP 9000 equipment with a 2-MHz probe was used for the examination of the intracranial circulation. The criteria of middle cerebral artery (MCA) stenosis used in this study were a peak systolic velocity (PSV) >140 cm/s or mean systolic velocity (MSV) >80 cm/s. For stenosis of the posterior circulation the criteria were PSV > 90 cm/s or MSV >60 cm/s. The data were obtained from 234 patients, and complete examinations were performed in 182 patients (77.7%). Ischemic stroke is the most common indication for performing TCD sonography. Stenosis was present in 38% of cases, with stenosis iof the anterior circulation being the more common. The most frequent risk factors were hypertension, dyslipidemia, and diabetes. Intracranial stenosis is common in stroke patients, in whom the risk factors are hypertension and diabetes.